2016
DOI: 10.1002/2016ja022373
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Alfvénic resonance layers in magnetic reconnection

Abstract: In the framework of two‐dimensional incompressible MHD, we investigate the formation of Alfvénic resonance layers with different super‐Alfvénic shear flows. It is found that Alfvénic resonance layers are formed in the inflow region for the cases with the shear flow thickness larger than the current sheet thickness. The Alfvénic layers exist at where the flow velocity is equal to the local Alfvén speed and slowly drift away from the current sheet region as a magnetic island develops. The ratio (D) between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Influences of fast super-Alfvénic shear flow on the KHIs are investigated with the resistive incompressible MHD simulations. It's found that in the presence of fast super-Alfvénic shear flow, first pair of Alfvén layers can appear in the inflow region away from the reconnection separatrices during magnetic reconnection similarly to our previous work [21], together with the second pair of layers formation when the initial asymptotic flow velocity reaches = v V 2.0 .…”
Section: Summary and Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Influences of fast super-Alfvénic shear flow on the KHIs are investigated with the resistive incompressible MHD simulations. It's found that in the presence of fast super-Alfvénic shear flow, first pair of Alfvén layers can appear in the inflow region away from the reconnection separatrices during magnetic reconnection similarly to our previous work [21], together with the second pair of layers formation when the initial asymptotic flow velocity reaches = v V 2.0 .…”
Section: Summary and Discussionsupporting
confidence: 77%
“…Meanwhile, the strong and close layers (i.e. the layer I) can sufficiently suppress the KHI and the reconnection process, which have already been investigated in our previous research [21]. It is clearly shown that the resonance layers become stronger from figures 1(c) to (d).…”
mentioning
confidence: 52%
See 3 more Smart Citations